Imatinib mesylate resistance and mutations: An Indian experience - Shweta Srivastava; Sarjana Dutt (Indian Journal of Medical and Paediatric Oncology)
The treatment of chronic myeloid leukemia (CML) has been revolutionized by the small molecule selective kinase inhibitor imatinib mesylate. Imanitib was the first BCR-ABL targeted agent approved for the treatment of CML patients and confers significant response in most patients; however, a substantial number of patients are initially refractory to the drug or may develop resistance during the course of treatment. Point mutations in the kinase domain (KD) of BCR-ABL that impact drug binding have been identified as one of the major mechanisms of resistance. We present here an overview of the current practice in monitoring for such mutations, including the methods used, criteria for investigating and guidelines for reporting the mutations. We further present and discuss the experience of our own laboratory in studying the KD mutations in Indian CML patients on imatinib treatment.